Letter (copy) : Situation in Spain - Tewson, Vincent
012b-0073-001 N.C.L. Secretary's. HVT/FC/235. D/S. 19th January, 1939. Mr. W.J.R. Squance, The Associated Society of Locomotive Engineers and Firemen, 9, Arkwright Road, Hampstead, N.W.3. Dear Mr. Squance, Situation in Spain. I have your letter of the 17th instant which will be reported to the National Council of Labour at their meeting on Tuesday next. Apart from immediate action which is being taken in regard to the general position the question will be discussed further by the National Council of Labour and also by the General Council next week. Yours sincerely, Assistant Secretary 292/946/12b/73